Improvement proposal for cost reduction through the implementation of a quality management system at Induamerica SL (LACCEI, 2024)
A research work was developed with the purpose of reducing costs through tools of the quality management system in the company Induamerica SL, for which diagnostic tools were used as: Ishikawa, Pareto, Histograms, Control charts, Process capacity and propositive tools, which are: Quality House (QFD), AMFE, DMAIC - SIX SIGMA. A total annual economic loss of S/29,194.60 was obtained and 4 main causes were identified: Lack of operator training, Lack of maintenance, Lack of standardization and Lack of control indicators also, after the proposal was implemented, it was improved in Z: 17%, 24%, 28% and 40%, respectively, and thus a global benefit of S/. 9,239.00 was obtained with an VAN of S/. 5.937,57 and the TIR of 51% demonstrating the viability of the proposed. All this because statistical control tools and the implementation of a correct quality management system significantly improve cost reduction and increase profitability in companies.